Persistent Vascular Complications in Long COVID: The Role of ACE2 Deactivation, Microclots, and Uniform Fibrosis - Christina-Michailia Sideratou; Christos Papaneophytou (MDPI AG, 2024)
Angiotensin-converting enzyme 2 (ACE2), a key regulator in vasoregulation and the renin-angiotensin system, is hypothesized to be downregulated in patients with COVID-19, leading to a cascade of cardiovascular complications. This deactivation potentially results in increased blood pressure and vessel injury, contributing to the formation and persistence of microclots in the circulation. Herein, we propose a hypothesis regarding the prolonged vascular complications observed in long COVID, focusing on the role of ACE2 deactivation and/or shedding, the persistence of microclots, and the unique pattern of fibrosis induced by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). Furthermore, we propose that the distinctive, uniform fibrosis associated with COVID-19, which is challenging to detect through conventional X-ray imaging, exacerbates vascular injury and impairs oxygenation. The persistence of these microclots and the unique fibrosis pattern are suggested as key factors in the extended duration of vascular complications post-COVID-19 infection, regardless of the initial disease severity. Moreover, plasma ACE2 activity has the potential to serve as prognostic or diagnostic biomarkers for monitoring disease severity and managing long COVID symptoms. Elucidating the role of ACE2 deactivation and the consequent events is vital for understanding the long-term effects of COVID-19. The experimental verification of this hypothesis through in vitro studies, clinical longitudinal studies, and advanced imaging techniques could yield significant insights into the pathophysiological mechanisms underlying long COVID, thereby improving the management of patients, particularly those with cardiovascular complications.